An In Vitro Pilot Study on the Effects of Silver Diamine Fluoride on Periodontal Pathogens and Three-Dimensional Scaffolds of Fibroblasts and Epithelium - Ho, Yolanda. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Periodontology.; Advisor: Driss Zoukhri.; Committee: Robert Gyurko, Guzin Uzel, Cheen Loo, Sarah Pagni, and Pinelopi Xenoudi.; Keywords: Microbiology, Dentistry, and Medicine.